If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 15 = 2c Reorder the terms: 15 + c = 2c Solving 15 + c = 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 15 + c + -2c = 2c + -2c Combine like terms: c + -2c = -1c 15 + -1c = 2c + -2c Combine like terms: 2c + -2c = 0 15 + -1c = 0 Add '-15' to each side of the equation. 15 + -15 + -1c = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1c = 0 + -15 -1c = 0 + -15 Combine like terms: 0 + -15 = -15 -1c = -15 Divide each side by '-1'. c = 15 Simplifying c = 15
| 6x^2+6x-12= | | 3t=t+32 | | 4q=q+15 | | 3m-1/4-2m-2/3=1 | | u+19=2u | | q+56=5q | | 240-1.6x=0 | | ([x^2+3]+[x-5])(6)= | | (x^2+3+x-5)(6)= | | (5v+3)(9+v)= | | 6x^3/24x^4 | | -23=45-4x | | 6g-3h= | | 3662x^5-21973x^4+52874x^3-63218x^2+37715x-8980=0 | | 20y^2+13y-15=0 | | 4x^2+28xy-18y= | | 14-7t=-56 | | 2x/3-16=-6 | | 13=y+3 | | X+49=3x-10 | | 6.0/2 | | 3x+2-15x=14y-6 | | -19-2d=11-8d | | -2s=-44+2s | | 7u-17=9u-5 | | 2x-90=-4x-18 | | -r-6r+2=86 | | 4x^4-9x^3= | | 6(p-10)-p=-40 | | -6y=-1-7y | | -17(12+w)=-7 | | (x-2)-12=(x-2)-12 |